CRL Ubiquitin Ligases and DNA Damage Response - Jin, Jianping; Li, Ju-Mei (Frontiers in Oncology, 2012)
Cullin/RING ubiquitin ligases (CRL) comprise the largest subfamily of ubiquitin ligases. CRLs are involved in cell cycle regulation, DNA replication, DNA damage response (DDR), development, immune response, transcriptional regulation, circadian rhythm, viral infection, and protein quality control. One of the main functions of CRLs is to regulate the DDR, a fundamental signaling cascade that maintains genome integrity. In this review, we will discuss the regulation of CRL ubiquitin ligases and their roles in control of the DDR.